EKSPLORASI KEPEKAAN DEWASA AWAL TERHADAP EKSPRESI WAJAH ANAK - Hartosujono Hartosujono (JURNAL PSIKOLOGI INSIGHT, 2017)
This study aims to determine the extent of psychological student's sensitivity to the facial expression of children. Facial expression is the symbol of emotion, when the child has a problem, their face showed the expression of their emotion. Whether the adults can guess what emotions of the children? A number of children are asked to view a number of images that can arouse their facial expression of their emotions to the images. Emotions that arose from the images were smiled, fear, sadness, anger, and disgust. Emotions of children arouse in 1 to 3 seconds, which is then photographed. The photos are selected based on the facial expression that best suits the emotions. The subject of this research was 222 students of Faculty of Psychology, with ranged 20-23 years old. The 60 male and 162 female students were asked to guess the emotions of one male child pictures and one female child which displays the five emotions in the face. The guesses of the students on the emotions of female child faces tend to be wrong on the expression of disgust that they guessed as sad. While in the male model photo, they failed to guess precisely the expression of the fear that they guessed as disgust.AbstrakPenelitian ini bertujuan untuk mengetahui sejauh mana kepekaan mahasiswa Psikologi terhadap ekspresi wajah anak. Ekspresi wajah seringkali menjadi fokus emosi, saat anak mengalami masalah, sangat tergambar sekali pada ekspresi wajahnya. Namun apakah interpretasi para orang dewasa tersebut sesuai dengan yang ditampilkan anak-anak tersebut. Sejumlah anak diminta melihat sejumlah gambar, agar memperlihatkan ekspresinya secara alami. Emosi yang timbul dari sejumlah gambar tersebut, adalah senyum, takut, sedih, marah, dan jijik. Emosi para anak timbul berkisar 1-3 detik, yang kemudian difoto. Foto-foto tersebut diseleksi, manakah foto ekspresi wajah paling sesuai dengan emosi yang timbul. Subjek penelitian ini adalah 222 mahasiswa Fakultas Psikologi, dengan kisaran usia 20-23 tahun. Terdapat 60 laki-laki dan 162 perempuan, mereka diminta menebak emosi 2 gambar pada anak beda jenis kelamin yang menampilkan dalam bentuk 5 emosi di wajah. Tebakan dari para mahasiswa pada emosi wajah perempuan cenderung tidak tepat pada ekspresi jijik yang cenderung ditebak sebagai sedih. Sedangkan pada foto model laki-laki cenderung tepat menebak ekspresi emosi takut yang cenderung ditebak sebagai jijik.